Full and Hollow Metal–Ceramic Beads Based on Tantalum and Alumina Produced by Alginate Gelation. Issue 8 (16th June 2022) - Storti, Enrico; Neumann, Marc; Zienert, Tilo; Hubálková, Jana; Aneziris, Christos G.
Abstract : Metal–ceramic composite beads containing different amounts of tantalum and alumina, particularly 100 vol% tantalum and 60–40 vol% tantalum/alumina, are produced by the alginate gelation process. Sodium alginate is used as gelling agent in the metal–ceramic suspension, while a calcium chloride solution is prepared to trigger the consolidation process. As in the previous study, different nozzles are used in order to obtain beads of three different sizes. The largest beads result to be hollow, and hence require a freeze‐drying step in order to prevent their collapse. After debinding in air, the composite beads are sintered at 1600 °C under inert atmosphere. Samples in green and sintered state are analyzed by digital light microscopy and scanning electron microscopy. Investigations by mercury intrusion porosimetry reveal that composite beads feature smaller pores compared to pure tantalum beads, as well as lower open porosity. The fracture strength is evaluated on single beads. Despite the high metallic content, both composite and pure tantalum beads show a brittle behavior. X‐ray powder diffraction (XRD) analyses reveal the presence of NaTaO 3, Ta 2 C 0.95, and AlTaO 4 alongside pure Ta in the samples prepared from pure tantalum. The impurities are due to reactions with Na, C, and Ca from the used additives. Abstract : Metal–ceramic composite beads containing tantalum and alumina are produced by the alginate gelation process and sintered at 1600 °C under inert atmosphere. Nearly spherical shapes and high porosities (>40 vol%) are obtained. Despite the high metallic content, all batches show a brittle behavior. Beta‐alumina, NaTaO3, Ta2 C0.95, and AlTaO4 are detected as secondary phases.